2017
DOI: 10.1093/mnras/stx3055
|View full text |Cite
|
Sign up to set email alerts
|

COSMOS2015 photometric redshifts probe the impact of filaments on galaxy properties

Abstract: The variations of galaxy stellar masses and colour-types with the distance to projected cosmic filaments are quantified using the precise photometric redshifts of the COSMOS2015 catalogue extracted from COSMOS field (2 deg 2 ). Realistic mock catalogues are also extracted from the lightcone of the cosmological hydrodynamical simulation HORIZON-AGN. They show that the photometric redshift accuracy of the observed catalogue (σ z < 0.015 at M * > 10 10 M and z < 0.9) is sufficient to provide 2D filaments that clo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
159
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(183 citation statements)
references
References 124 publications
(119 reference statements)
21
159
1
1
Order By: Relevance
“…Galaxies are significantly ∼ 10% more massive, and ∼ 10% less star-forming. This trend is expected since the excess of passive galaxies near the filaments spines was already shown in several studies (e.g., Malavasi et al 2017;Laigle et al 2018;Kraljic et al 2018;Sarron et al 2019). This implies a different ratio of passive over active galaxies with increasing distance to the filaments' spine, producing these gradients.…”
Section: Average Propertiessupporting
confidence: 70%
“…Galaxies are significantly ∼ 10% more massive, and ∼ 10% less star-forming. This trend is expected since the excess of passive galaxies near the filaments spines was already shown in several studies (e.g., Malavasi et al 2017;Laigle et al 2018;Kraljic et al 2018;Sarron et al 2019). This implies a different ratio of passive over active galaxies with increasing distance to the filaments' spine, producing these gradients.…”
Section: Average Propertiessupporting
confidence: 70%
“…Using the Sloan Digital Sky Survey (SDSS, York et al 2000), Chen et al (2017) find that at the same local density, galaxies that reside closer to filaments are more massive than those further out, in agreement with Alpaslan et al (2016) and Laigle et al (2018). Using the same survey, but at intermediate redshifts, 0.12 < z < 0.40, Zhang et al (2013) detect an evolution in the blue fraction of filament galaxies located in between pairs of clusters, that is not observed in clusters.…”
Section: Introductionmentioning
confidence: 82%
“…Using the same survey, Alpaslan et al (2016) have found that isolated spiral galaxies have higher stellar masses and lower SFR towards the inner regions of filaments than in the filament periphery. Similarly, Laigle et al (2018) study the properties of galaxies with photo-metric redshifts in the range 0.5 < z phot < 0.9 and find that, at fixed stellar mass, passive galaxies are more confined towards the core of filaments.…”
Section: Introductionmentioning
confidence: 98%
“…Their dynamical evolution probes the underlying cosmological model. They also play an important environmental role on galaxy formation and galaxy properties (Hahn et al 2007;Sousbie et al 2008;Pichon et al 2011;Codis et al 2012;Malavasi et al 2017;Laigle et al 2017). However, given the low-density contrast of filaments, identifying them in observations has remained a challenge and, in this context, several observables have been devised to probe their mass distribution.…”
Section: Introductionmentioning
confidence: 99%